76.0k views
20 votes
If the distance of P x, y from the points A (3, 6) and B −3, 4 are equal, prove that

3x + y = 5

User Jonnus
by
5.3k points

1 Answer

4 votes

Answer:

See Below.

Explanation:

We are given a point P(x, y). It is equidistant from A(3, 6) and B(-3, 4).

So, let's first determine the distance from P to each point. We can use the distance formula:


d=√((x_2-x_1)^2+(y_2-y_1)^2)

Segment PA:

We will let P(x, y) be (x₂, y₂) and A(3, 6) be (x₁, y₁). By substitution:


d=\sqrt{(x-3)^2+(y-6)^2

This represents the distance from P to A.

Segment PB:

Again, we will let P(x, y) be (x₂, y₂) and B(-3, 4) be (x₁, y₁). By the distance formula:


d=√((x-(-3))^2+(y-4)^2)

We may simplify:


d=√((x+3)^2+(y-4)^2)

Now, we know that the two distances are equivalent. Hence:


√((x-3)^2+(y-6)^2)=\sqrt{(x+3)^2+(y-4)^2

Simplify. Square both sides:


(x-3)^2+(y-6)^2=(x+3)^2+(y-4)^2

Square:


(x^2-6x+9)+(y^2-12x+36)=(x^2+6x+9)+(y^2-8x+16)

Subtract all terms from the right:


(x^2-6x+9)-(x^2+6x+9)+(y^2-12x+36)-(y^2-8x+16)=0

Distribute the negative:


[(x^2-6x+9)+(-x^2-6x-9)]+[(y^2-12y+36)+(-y^2+8y-16)]=0

Rearrange:


[(x^2-x^2)+(-6x-6x)+(9-9)]+[(y^2-y^2)+(-12y+8y)+(36-16)]=0

Combine like terms;


(-12x)+(-4y)+(20)=0

We can divide both sides by -4:


3x+y-5=0

Finally, adding 5 to both sides produces:


3x+y=5

User Zingi
by
5.3k points